The role of mobile service providers in combating mobile bullying among adolescent in South Africa - Willie, Dickson (Department of Information Systems, 2017)
Modern-day mobile communications technology has advanced in rapid phases, triggered by the presence of mobile technology applications. This advancement has accelerated the notion of enriched data, information and services that individuals have access to. The value presented to users of mobile technology in terms of limitless access to a wealth of enriched data is beneficial to society. However, this benefit window also exposed the users into a virtual sphere that is riddled with a wide variety of subtle and overt risks; mobile service providers have lawful responsibilities and concrete moral obligations to protect their customers. It is for this purpose that the researcher focused on examining the extent to which mobile service providers are assisting society to combat the new phenomenon of mobile bullying. A deductive research approach was followed in this study, and a conceptual model was developed to examine the extent of the involvement of the mobile service providers in reducing mobile bullying. The sampling method used in this study is a purposive or judgemental sampling method to obtain data from four (4) major mobile service providers. In the empirical evidence, it has been found that service providers have sufficient knowledge of the law that governs them in distributing mobile content in order to protect minors from the harmful content. Furthermore, another key finding indicates that the service providers' input is inadequate by way of providing education programs to assist mobile users and society in an effort to combat the new phenomenon of mobile and cyber-bullying. This study can act as a base for future research into examining the extent of the role of mobile service providers in reducing mobile bullying, educating society about mobile bullying as well as informing mobile service providers about the importance of their role in combating mobile bullying.